Efektifitas Kombinasi Pijat Oksitosin dan Hypno Breastfeeding terhadap Optimalisasi Produksi ASI pada Ibu Nifas - Fitriani Ningsih; Rizki Muji Lestari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
One of the factors that influence the smooth production of breast milk is the physical and psychological condition of the puerperal mother. Mother's milk. In connection with the problems mentioned above, it is very necessary to be solved and resolved, one of them by providing interventions between oxytocin massage and Hypno breastfeeding. Hypno breastfeeding is one of the preparation of the mother in terms of mind. The purpose of this study was to look at the workings of oxytocin and Hypno breastfeeding therapy on the Optimization of Breast Milk Production in Postpartum Mothers. The design of this study used a quasi-experimental research design (Rapid Experiment) with a design only Posttest Design with Quarter Groups, using a sample of 30 postpartum mothers respondents in the postpartum hospital dr. Doris Sylvanus Palangkaraya City. This group was divided into 15 respondents as an intervention group and 15 respondents as a control group. In this study using the Chi-Square statistical test. Based on the results of the study obtained P-value = 0.020 with the provisions of the value of p <0.05, then the P value> which can be concluded that the combination of oxytocin massage and Hypno breastfeeding is very effective for optimizing breast milk production in postpartum mothers. And from the statistical test results obtained an OR value of 7.4 (CI 1.222-45.005) meaning that the combination of oxytocin massage and Hypno breastfeeding has a 7.4 chance to optimize milk production.